2022
DOI: 10.1007/s11440-022-01536-2
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-biocement composite treatment for stabilisation of soil against both current and wave erosion

Abstract: Increased frequency of extreme weather events has made the conservation of riverbanks and coastlines a global concern. Soil stabilisation via microbially induced calcite precipitation (MICP) is one of the most eco-suitable candidates for improving resilience against erosion. In this study, the erosion characteristics of soil treated with various levels of biocementation are investigated. The samples were subjected to hydraulic flow in both tangential and perpendicular directions in a flume to simulate riverban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In previous studies, it has been established that the biopolymer treatment for sandy soil is not suitable due to the hydrophilic nature of XG and the lack of the chance of Thermal conductivity (W/m*K) TH-02-069 formation of stable cationic bonds due to the scarcity of clay particles [9,12,24]. However, studies on fine-grained soils have established that the clayey soils treated with XG are substantially more stable [8,16,17,26].…”
Section: Influence Of Biopolymer Amendment On Erosion Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been established that the biopolymer treatment for sandy soil is not suitable due to the hydrophilic nature of XG and the lack of the chance of Thermal conductivity (W/m*K) TH-02-069 formation of stable cationic bonds due to the scarcity of clay particles [9,12,24]. However, studies on fine-grained soils have established that the clayey soils treated with XG are substantially more stable [8,16,17,26].…”
Section: Influence Of Biopolymer Amendment On Erosion Resistancementioning
confidence: 99%
“…Recent studies reported that the addition of biopolymers such as Xanthan Gum (XG) to soil could improve the strength and erosion resistance significantly [8][9][10][11][12][13][14][15][16][17]. However, the application of biopolymers in view of preparing an ECM has not been well explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of geotechnical engineering, the research results of MICP on soil improvement can be used for foundation reinforcement [ 57 , 58 , 59 ], earth dam reinforcement [ 60 ], wind prevention, sand fixation [ 61 ], reservoir bottom anti-seepage, and anti-seepage curtains [ 42 ]. In the field of agricultural production and construction, MICP technology also plays a beneficial role in improving soil mass, such as water and soil conservation, the prevention of water and soil loss [ 62 ], and stability improvement in agricultural water conservancy projects [ 63 ] and agricultural buildings [ 64 ], which is conducive to planting and production activities and also ensures safety. Testing the mechanical properties of the cemented samples can not only measure the quality of the cementation effect but can also determine the feasibility of using the MICP technology based on urea hydrolysis to improve the soil.…”
Section: Introductionmentioning
confidence: 99%